Mamão (Carica papaya L.) liofilizado em pó: avaliação das características físicas, físico-químicas e higroscópicas - Canuto, Holivânia Maria Pereira (2011)
Papaya (Carica papaya L.) is a tropical fruit known and appreciated worldwide. Their sensory and nutritional characteristics contribute to the wide acceptability of this fruit. However, in the post-harvest loss is high due to its highly perishable. In this context, the lyophilization appears as a promising process for dehydration of papaya, because is a drying process that contributes to preserve the vitamin and mineral components of food. In this work, was applied the lyophilization process in Formosa papaya pulp, being used for two of the three trials studied the adjuvant lyophilization maltodextrin. Was evaluated the stability of food powders obtained through of the study of the physical, physico-chemical and hygroscopic characteristics. The lyophilization significantly reduced the carotenoid contents of the pulps. The high sugar contents of the pulps were kept until the end of the storage the powders obtained after lyophilization. The increase in concentration of the adjuvant resulted in higher retention of vitamin C during storage, as well as reduced the hygroscopicity in papaya lyophilized powders, resulting in increased stability of the water activity and maintenance of humidity levels. Therefore, showed the relevance of maltodextrin as an adjuvant to lyophilization of the pulp of Formosa papaya, providing food powders more viable, including increasing the shelf life of these products.